2009
DOI: 10.1002/cne.21980
|View full text |Cite
|
Sign up to set email alerts
|

Cortical connections of the visuomotor parietooccipital area V6Ad of the macaque monkey

Abstract: Area V6A, a functionally defined region in the anterior bank of the parietooccipital sulcus, has been subdivided into dorsal and ventral cytoarchitectonic fields (V6Ad and V6Av). The aim of this study was to define the cortical connections of the cytoarchitectonic field V6Ad. Retrograde and bidirectional neuronal tracers were injected into the dorsal part of the anterior bank of parietooccipital sulcus of seven macaque monkeys (Macaca fascicularis). The limits of injection sites were compared with those of cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
143
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(161 citation statements)
references
References 109 publications
(18 reference statements)
16
143
2
Order By: Relevance
“…V6A is a parietal area receiving visual information (Galletti et al, 1996;1999;Gamberini et al, 2009) as well as somatosensory-and movement-related signals relative to reach and grasp actions (Galletti et al, 1997;Fattori et al, 2001;Breveglieri et al, 2002;Fattori et al, 2005;Fattori et al, 2009;Fattori et al, 2010). The present study was designed to determine whether and how the vision of the moving limb influences the activity of V6A neurons during reaching movements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…V6A is a parietal area receiving visual information (Galletti et al, 1996;1999;Gamberini et al, 2009) as well as somatosensory-and movement-related signals relative to reach and grasp actions (Galletti et al, 1997;Fattori et al, 2001;Breveglieri et al, 2002;Fattori et al, 2005;Fattori et al, 2009;Fattori et al, 2010). The present study was designed to determine whether and how the vision of the moving limb influences the activity of V6A neurons during reaching movements.…”
Section: Discussionmentioning
confidence: 99%
“…The functional properties of V6A neurons clearly reflect (and are likely the functional consequence of) the anatomical connections of this area. In fact, V6A receives projections directly from dorsal premotor cortex (Matelli et al, 1998;Shipp et al, 1998;Marconi et al, 2001;Gamberini et al, 2009), and the extrastriate visual area V6 . Both neuronal properties and anatomical connections of V6A indicate that visual, somatosensory and motor signals interact and possibly become integrated in V6A .…”
Section: Introductionmentioning
confidence: 99%
“…It receives input from the posterior parietal areas LIP and PG (Gamberini et al, 2009), where vergence angle has been reported to have an effect on presaccadic and fixation activities, respectively (Sakata et al, 1980;Genovesio and Ferraina, 2004). Also the area MIP is strongly and reciprocally connected with V6A (Gamberini et al, 2009;Passarelli et al, 2011), and it is known that MIP (also named PRR) hosts neurons with planning activity for reaching modulated by fixation depth (Bhattacharyya et al, 2009) et al, 2011). Modulations of neural activity by fixation depth have been also found in the VIP (ventral intraparietal) area (Colby et al, 1993) and in visual areas V2 and V4 (Dobbins et al, 1998;Rosenbluth and Allman, 2002), all directly connected with V6A.…”
Section: Comparison With Other Areasmentioning
confidence: 99%
“…The present work was designed to test whether eye version and vergence modulate neuronal activity in V6A, a cortical area located in the medial part of monkey PPC (Galletti et al, 1996(Galletti et al, , 1999a. V6A is strongly connected with PPC areas that encode eye movements and fixations in depth, like the lateral intraparietal area (LIP) and area 7a (Gamberini et al, 2009;Passarelli et al, 2011). It also contains neurons modulated by arm-reaching movements in 3D space Marzocchi et al, 2008;Bosco et al, 2010), and by gaze position in a frontoparallel plane (Galletti et al, 1995;Nakamura et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and experimental studies have demonstrated that areas located on the medial cortex near the occipitoparietal transition are important for "online" visual control of motor activity (Galletti et al, 2003;Gamberini et al, 2009). While it has been suggested that DM provides crucial inputs for this type of sensorimotor coordination (Rosa and Tweedale, 2001), there are good reasons to suspect that this area also contributes to other visual functions.…”
Section: Introductionmentioning
confidence: 99%